Recent developments in the clinical pharmacology of rolapitant: subanalyses in specific populations - Rapoport, Bernardo L.; Jordan, Karin (Drug design, development and therapy, 2017)
Abstract: Knowledge of the involvement of the neurokinin substance P in emesis has led to the development of the neurokinin-1 receptor antagonists (NK-1 RAs) for control of chemotherapy-induced nausea and vomiting (CINV), in combination with serotonin type 3 receptor antagonists and corticosteroids. The NK-1 RA rolapitant, recently approved in oral formulation, has nanomolar affinity for the NK-1 receptor, as do the other commercially available NK-1 RAs, aprepitant and netupitant. Rolapitant is rapidly absorbed and has a long half-life in comparison to aprepitant and netupitant. All three NK-1 RAs undergo metabolism by cytochrome P450 (CYP) 3A4, necessitating caution with the concomitant use of CYP3A4 inhibitors, but in contrast to aprepitant and netupitant, rolapitant does not inhibit or induce CYP3A4. However, rolapitant is a moderate inhibitor of CYP2D6, and concomitant use with CYP2D6 substrates with narrow therapeutic indices should be avoided. Aprepitant, netupitant, and rolapitant have all demonstrated efficacy in the control of delayed CINV in patients receiving moderately and highly emetogenic chemotherapy in randomized controlled trials, including over multiple cycles of chemotherapy. We reviewed recent post hoc analyses of clinical trial data demonstrating that rolapitant is efficacious in the control of CINV in patient populations with specific tumor types, namely, breast cancers, gastrointestinal/colorectal cancers, and lung cancers. In addition, we show that rolapitant has efficacy in the control of CINV in specific age groups of patients receiving chemotherapy (<65 and ≥65 years of age). Overall, the safety profile of rolapitant in these specific patient populations was consistent with that observed in primary analyses of phase 3 trials. Keywords: rolapitant, neurokinin-1 receptor antagonist, chemotherapy-induced nausea and vomiting, post hoc analyses
Gesehen am 31.07.2018